Curly Chili Commodity Marketing Pattern (Capsicum Annum L) (Case Study: of Curly chili Traders in the Gosalaha Market, Tidore City, North Maluku - Saban, Julia; Azizah HS, Nur; Abdurachman, Maman (Agrikan Jurnal Agribisnis Perikanan, 2023)
This research aims to analyze the marketing channel, the size of the margin and the profit level of curly chili marketing in the Gosalaha Market, Tidore Islands City. This research was conducted at the Gosalaha Market, Tidore City Islands, on the grounds that it is a trading center for traders. The research time was carried out for approximately 2 months, starting from November to December 2022 starting from data collection to compiling research results. This research uses descriptive analysis method. Data Collection Techniques by Observation, Interview and Documentation. The results showed that the curly chili marketing pattern at Gosalaha Market, Tidore City includes 2 marketing patterns, namely, curly chili marketing pattern 1, curly chili marketing pattern 2.